PENGEMBANGAN HANDOUT DENGAN TAMPILAN MAJALAH PADA MATERI SISTEM GERAK PADA MANUSIA UNTUK SMP KELAS VIII - Utami, Purnama Sari (Pendidikan Biologi, 2014)
The material teaching like handout hasnât been used in this school, to support studying process, teacher use material like Lembar Kerja Siswa (LKS). The material of teaching which is teacher use is still not interesting yet, the picture is not colorful, the picture information is not clear and not practice so that student got difficulty in understanding the material in learning process including human movement system material. Because of that, it need the development material like handout by magazine view in human movement system material. This research purpose to produce valid handout and practice by magazine view in human movement system material for class VIII. Knowing the validity and practicality of handout with magazine view in human movement system material for class VIII developed. This research is a development research by procedural model which is consist of define ,design, and develop . this research is done in STKIP PGRI West Sumatra and SMPN 10 Padang class IX in odd semester year 2013/2014. The subject of this consist of 5 validation, and to test the practicality is 0done by 2 teacher and 32 students in human movement system material. The data result of research show that validity value of handout in average is valid category 87,83%. The result of practicality of handout by magazine view of teacher with category very practice 90,83% as average, meanwhile by the student in human movement system material value is 87,30%. So the average of practicality of handout for human movement system material is 89,06%. Based on the research result which is done, it can be concluded that handout by magazine view in human movement system material for SMP is completely valid and practice criteria.